THE ROLE OF INTERACTIVE GAMES IN LEARNING ENGLISH - Abdug’ofurov Shohrux Sherali o’g’li,; Khaydarova Shoira Toxir qizi, (TADQIQOTLAR, 2026)
Abstract: This article discusses the role of interactive games in helping students acquire English, increasing engagement, motivation, and the development of language skills.  Resources  like  Kahoot,  Wordwall,  Bingo,  and  Charades  are  analyzed  to  be effective classroom tools to make mundane classroom sessions fun and entertaining. The  above-mentioned  observations  make  it  clear  that  games  encourage  increased participation,  reduce  the  hesitancy  of  learning,  and  retain  memories  through  the emphasis of core areas of the language skill, like speaking, listening, and vocabulary development.